2015
DOI: 10.1016/j.media.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Automatic multi-resolution shape modeling of multi-organ structures

Abstract: Point Distribution Models (PDM) are among the most popular shape description techniques and their usefulness has been demonstrated in a wide variety of medical imaging applications. However, to adequately characterize the underlying modeled population it is essential to have a representative number of training samples, which is not always possible. This problem is especially relevant as the complexity of the modeled structure increases, being the modeling of ensembles of multiple 3D organs one of the most chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Multi-organ segmentation has attracted considerable interest over the years. Classical approaches include statistical shape models (Cerrolaza et al, 2015;Okada et al, 2015), and/or employ techniques based on image registration. So called multi-atlas label fusion (Rohlfing et al, 2004;Wang et al, 2013;Iglesias and Sabuncu, 2015) has found wide application in clinical research and practice.…”
Section: Related Workmentioning
confidence: 99%
“…Multi-organ segmentation has attracted considerable interest over the years. Classical approaches include statistical shape models (Cerrolaza et al, 2015;Okada et al, 2015), and/or employ techniques based on image registration. So called multi-atlas label fusion (Rohlfing et al, 2004;Wang et al, 2013;Iglesias and Sabuncu, 2015) has found wide application in clinical research and practice.…”
Section: Related Workmentioning
confidence: 99%
“…Endoscope navigation through the gastrointestinal tract could benefit from segmentations of multiple gastrointestinal and surrounding organs. Many previous studies have proposed methods for multi-organ segmentation of abdominal CT, principally based on multi-atlas segmentation [16,9,14,13,12] or statistical shape models [2,9]. Organs surrounding the GI tract, such as the liver and pancreas, are included in many of these studies, but esophagus and stomach segmentation has received little attention, likely due to the lack of available reference segmentations.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-organ segmentation has been the subject of extensive study. The most common approaches, statistical shape models [2,9] and multi-atlas label fusion [16,9,14,13,12], rely on registration to establish anatomical correspondence. However, interpatient image registration is less accurate for abdominal imaging than for other anatomical sites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GlM► Akhoundi- Asl and Soltanian-Zadeh, 2007;Bossa and Olmos, 2006;Bossa and Olmos, 2007;Bossa et al, 2011;Cootes et al, 1994;Duta and Sonka, 1998;Gorczowski et al, 2010;Poupon et al, 1998;Styner et al, 2006;InM► Akhoundi-Asl and Soltanian-Zadeh, 2007;Asl and Soltanian-Zadeh, 2008;CoDeM► Bazin and Pham, 2006;Fan et al, 2008a;Fan et al, 2008b;Gao et al, 2011;Gao et al, 2017;Han and Prince, 2003;Han et al, 2002;Ho and Shi, 2004;Holtzman-Gazit et al, 2003;Jeon et al, 2005;Kim et al, 2014;Litvin and Karl, 2005;MacDonald et al, 1994;Mangin et al, 1995;Merino-Caviedes et al, 2010;Pohl et al, 2007;Samson et al, 2000;Tsai et al, 2001;Uzunbas et al, 2010;Vese and Chan, 2002;Yan et al, 2009;Yang et al, 2004;Zeng et al, 1999;MuLeM► Cerrolaza et al, 2011;Cerrolaza et al, 2012;Cerrolaza et al, 2014;Cerrolaza et al, 2015;Cerrolaza et al, 2016;Joohwi Leea, Sun Hyung Kimb, 2016;Shen et al, 2001;…”
Section: Brainmentioning
confidence: 99%